The Films (Blackfriars, 1947)
Sociology of Film. By J. P. Mayer. America at the Movies. By Margaret Farrand Thorp. The Factual Film: A survey by the Arts Enquiry. Science and the Meanings of Truth. By Martin Johnson. The Timeless Moment. By Warner Allen. (Faber; 10s. 6d.) Politics and Morals. By Benedetto Croce, translated by S. J. Castiglione. (Allen and Unwin; 8.s. 6d.) Whatsoever He Shall Say: the first Theophila Correspondence. By Ferdinand Valentine, O.P. (Blacktriars Publications, Oxford; 5s.) Justin McCann, O.S.B. A Catholic History of Weston-in-arden (1849–1929). By Rev. J. B. Hickson. Philosophia Moralis Generalis. By E. T. Toccafondi, O.P.